Women Lovers, or The Third Woman - Barney, Natalie Clifford (Book collections on Project MUSE., 2016)
This long-lost novel recounts a passionate triangle of love and loss among three of the most daring women of belle epoque Paris. In this barely disguised roman à clef, the legendary American heiress, writer, and arts patron Natalie Clifford Barney, the dashing Italian baroness Mimi Franchetti, and the beautiful French courtesan Liane de Pougy share erotic liaisons that break all taboos and end in devastation as one unexpectedly becomes the "third woman." Never before published in English, and only recently published in French, this modernist, experimental work has been brought to light by Chel.